Arterial Blood Gas Tensions and pH in Acute Asthma in Childhood. Issue 5616 (24th August 1968) - Simpson, H.; Forfar, J. O.; Grubb, D. J.
Abstract : Studies of the arterial blood gas tensions and pH in 21 children during 24 acute attacks of asthma showed that all were hypoxic on admission to hospital, and in 10 there was evidence of carbon dioxide retention. Cyanosis, invariably present when the So2 was below 85%, and restlessness in patients breathing air were the most reliable indices of the severity of hypoxia. There were no reliable clinical guides to the Pco2 level. Conventional oxygen therapy in tents (25–40%) did not always relieve hypoxia, and in three cases the administration of oxygen at a concentration of 40% or over failed to produce a normal arterial oxygen tension. Uncontrolled oxygen therapy may aggravate respiratory acidosis, and three of our patients developed carbon dioxide narcosis while breathing oxygen. The necessity for blood gas measurements in the management of severe acute asthma in childhood is emphasized.